2003
DOI: 10.1046/j.1098-1616.2003.030.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Demand for Life Insurance

Abstract: For almost 50 years researchers have sought to explain consumer behavior concerning the purchase of life insurance. This study examines the literature relating to specific demographic and economic factors that may be identifiable as traits influencing the demand for life insurance, and discusses general environmental issues that may relate to life insurance demand. By organizing the wealth of literature in a useful and systematic format, noting consistencies and contradictions, this examination seeks to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 69 publications
(128 reference statements)
4
114
0
2
Order By: Relevance
“…More than 20 empirical academic studies have been published on the effect of key factors on demand for life insurance. These factors are: demographic, macroeconomic, social and psychological, institutional, as well as those depending on the insurers themselves (Zietz, 2003). Many authors indicate to the importance of inflation rate, available income of citizens, financial development of the country, social security, as well as population (for example, birthrate, life expectancy, educational level, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 20 empirical academic studies have been published on the effect of key factors on demand for life insurance. These factors are: demographic, macroeconomic, social and psychological, institutional, as well as those depending on the insurers themselves (Zietz, 2003). Many authors indicate to the importance of inflation rate, available income of citizens, financial development of the country, social security, as well as population (for example, birthrate, life expectancy, educational level, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…legal factors (corruption, the rule of law etc.) (Sen and Madheswaran, 2013;Sen, 2007;Hwang and Greenford, 2005;Zietz, 2003;Beck and Webb, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…7. Bernheim (1991) and Zietz (2003) showed that the bequest motive has a significant impact on life insurance demand. 8.…”
Section: U X Xmentioning
confidence: 99%
“…Zietz (2003) provides a summary of the literature in the field, pointing out both the socio-demographic determinants, such as age of the insured person, the desire to bequeath posterity, education, youth dependency ratio and marital status, and also the economic and financial ones, such as income and insured savings, inflation, social security and the level of real interest rate, among others. The results are mixed, in part due to the different degree of development of life insurance markets.…”
Section: Introductionmentioning
confidence: 99%